The B-3 Ethylene Response Factor MtERF1-1 Mediates Resistance to a Subset of Root Pathogens in Medicago truncatula without Adversely Affecting Symbiosis with Rhizobia - Anderson, J.; Lichtenzveig, Judith; Gleason, C.; Oliver, Richard; Singh, K (2010)
The fungal necrotrophic pathogen Rhizoctonia solani is a significant constraint to a range of crops as diverse as cereals, canola, and legumes. Despite wide-ranging germplasm screens in many of these crops, no strong genetic resistance has been identified, suggesting that alternative strategies to improve resistance are required. In this study, we characterize moderate resistance to R. solani anastomosis group 8 identified in Medicago truncatula. The activity of the ethylene- and jasmonateresponsive GCC box promoter element was associated with moderate resistance, as was the induction of the B-3 subgroup of ethylene response transcription factors (ERFs). Genes of the B-1 subgroup showed no significant response to R. solani infection. Overexpression of a B-3 ERF, MtERF1-1, in Medicago roots increased resistance to R. solani as well as an oomycete root pathogen, Phytophthora medicaginis, but not root knot nematode. These results indicate that targeting specific regulators of ethylene defense may enhance resistance to an important subset of root pathogens.We also demonstrate that overexpression of MtERF1-1 enhances disease resistance without apparent impact on nodulation in the A17 background, while overexpression in sickle reduced the hypernodulation phenotype. This suggests that under normal regulation of nodulation, enhanced resistance to root diseases can be uncoupled from symbiotic plant-microbe interactions in the same tissue and that ethylene/ERF regulation of nodule number is distinct from the defenses regulated by B-3 ERFs. Furthermore, unlike the stunted phenotype previously described for Arabidopsis (Arabidopsis thaliana) ubiquitously overexpressing B-3 ERFs, overexpression of MtERF1-1 in M. truncatula roots did not show adverse effects on plant development.